A Google Earth Database of Central American Volcanic Vents - Carr, Michael J. (Revista geológica de América central, 2017)
Satellite imagery in Google Earth reveals 807 volcanic vents for Central America. Most of these have already been recognized. In fact, previous catalogs include many volcanoes that are not obvious in Google Earth and they are not included here. Furthermore, 47 large but deeply eroded volcanoes are not included because they appear very old. On the other hand, many young vents may be obscured in areas of low quality imagery or in areas of dense cloud forest. High quality Google Earth coverage keeps expanding so this catalog can be improved with time. Lidar imagery would greatly improve vent detection. A significant problem with any list of volcanic features is determining the appropriate cutoff age. Topographic expression is the only available criterion for estimating age for most of the vents and this criterion is highly flawed because of differences in volcanic deposits, weathering, annual rainfall and other factors. Ideally, 40Ar/39Ar ages would be available for most of the volcanoes and the revealed space-time pattern of volcanic activity would allow improved hazard estimates as well as a deeper understanding of the causes and controls of volcanism. Instead, the database is a necessary step toward: a) recognizing important volcanological problems that can attract geochronological research funding and b) encouraging a long-term campaign for determining the temporal development of Central American volcanism. The database is intended as a draft to be used and improved, not a fixed list.